Effects of ? irradiation on the characteristics of the Cu-13wt.%Al-4wt.%Ni shape memory alloy - Zengin, R; Ceylan, M (Elsevier, 2004)
Transformation temperatures, activation energies and lattice parameters of unirradiated and irradiated Cu-13wt.%Al-4wt.%Ni shape memory samples were determined using differential scanning calorimetry (DSC), electrical resistivity change (ERC) measurements and X-ray diffraction (XRD) techniques. After 15 kGy gamma irradiation, the transformation temperatures, and activation energies decrease and some changes in the latent heat of formation and lattice parameters also occur. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: shape memory alloy; gamma irradiation; transformation temperatures; activation energies